Hemostatic Abnormalities in Patient with Liver Cirrhosis: A Review - Wahyuni Wahyuni; Diana Novita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Liver cirrhosis is one of Indonesia’s most common liver diseases, where the incidence is 38 – 52.8% of all liver diseases. Liver cirrhosis refers to a late-stage pathological lesion caused by the accumulation of extracellular matrix in the liver parenchyma. Liver cirrhosis is caused by chronic injury to the liver due to viral infections, autoimmune, toxins, cholestasis, metabolic diseases, and other diseases. Patients with cirrhosis, especially decompensated liver cirrhosis, often have a variety of comorbidities. One of the complications that occur is a disturbance in the hemostasis system. Disorders of hemostasis in these patients can occur at the stage of primary hemostasis, secondary, or fibrinolysis. This situation causes patients with liver cirrhosis to be at risk for developing thrombotic and/or coagulation disorders. It was important to evaluate a patient with liver cirrhosis is at risk for hemostasis disorders based on the background. This literature review discusses disorders of hemostasis in patients with liver cirrhosis accompanied by diagnosis and treatment.